New constraints on global geochemical cycling during oceanic anoxic event 2 (Late Cretaceous) from a 6-million-year long molybdenum-isotope record - Dickson, AJ; Jenkyns, HC; Idiz, E; Sweere, TC; Murphy, MJ; van den Boorn, SHJM; Ruhl, M; Eldrett, JS; Porcelli, DR (American Geophysical Union, 2021)
Intervals of extreme warmth are predicted to drive a decrease in the oxygen content of the oceans. This prediction has been tested for the acme of short (<1 million years) episodes of significant marine anoxia in the Phanerozoic geological record known as Oceanic Anoxic Events (OAEs). However, there is a paucity of data spanning prolonged multimillion-year intervals of geological time before and after OAEs. We present a Mo-isotope record from limestones and marlstones of the Eagle Ford Group, South Texas, which was deposited in the southern Cretaceous Western Interior Seaway of North America during a 6-million-year period encompassing OAE 2 (Late Cenomanian–early Turonian: ∼94 Ma). Mo-isotope compositions from deposits that formed in euxinic (sulfidic) conditions before OAE 2 allow the paleo-seawater composition to be constrained to 1.1%–1.9%. This range of values overlaps previous estimates of up to ∼1.5% for the peak of OAE 2 determined from similarly sulfidic sediments deposited in the restricted proto-North Atlantic Ocean. Mo-isotopes thus varied by less than a few tenths of per mil across one of the most extreme intervals of global deoxygenation in the Late Phanerozoic. Rather than a limited change in oceanic deoxygenation, we suggest that the new data reflect changes to global iron cycling linked to basalt-seawater interaction, terrestrial weathering and expanded partially oxygenated shallow shelf-seas that played a key role in the burial of isotopically light molybdenum, thus acting as a counterbalance to its removal into sulfidic sediments.